Karyotypic analyses and genomic affinity among Argentinean species of Passiflora - Bugallo, Veronica Lucia; Realini, María Florencia; Facciuto, Gabriela Rosa; Poggio, Lidia (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2021)
The genus Passiflora (Passifloraceae) has more than 500 species, nineteen are native to Argentina. By their austral distribution, these species were included in breeding programs to obtain ornamental varieties tolerant to low temperatures. The aim of this work was to know the cytogenetic characteristics of Passiflora genotypes present in a working collection, as an indispensable knowledge for the development of a breeding plan. Chromosomal preparations were performed and karyotypic characteristics, rDNA sites by FISH and affinity among subgenera by GISH were studied. Chromosome counts in fourteen Argentinean species confirmed the basic chromosome numbers previously published: x = 6 for subgenus Decaloba, x = 9 for subgenus Passiflora and x = 10 for Dysosmia. The karyotypic parameters (karyotype, haploid chromosome length and asymmetry indices) and genomic affinities among the subgenera, clarify most of the chromosomal evolution of the genus. The results obtained strongly suggest that the basic number x = 6 would be the original one and that x = 9 was originated by processes of polyploidy and descendent dysploidy. Since subgenus Passiflora possesses the largest genomes, it is postulated that evolutionary process leading to x = 9 was accompanied by unequal distribution of non-coding repetitive DNA, mainly transposable elements. These processes could explain the asymmetrical karyotypes of species of subgenus Passiflora.